The Effects of Cadmium on Fatty Acid Composition in the Muscle and Skin of Juvenile Rainbow Trout (Oncorhynchus mykiss, Walbaum 1792) - Konar, Vahit; Aydogmus, Ciler; Orun, Ibrahim; Kandemir, Sevket (Medwell Online, 2010)
In this study, the effect of 1 mg L-1 (ppm) dose of Cadmium (Cd) on fatty acid composition in the muscle and skin tissues of farmed rainbow trout has been investigated. The effect of Cd was evaluated for 72 h of exposure times. Palmitic acid (16:0), palmitoleic acid (16:1), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2), linolenic acid (18:3), arachidonic acid (20:4), eicosapentaenoic acid (20:5), docosapentaenoic acid (22:5) and docosahekzaenoic acid (22:6) in fatty acid composition of both skin and muscle tissues have been found. While they were observed that the amounts of palmitic acid, stearic acid increased, palmitoleic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosapentaenoic acid and docosahekzaenoic acid decreased in the skin and muscle tissues in fish exposed to the Cd compared with control groups. It was also found that Cd had reduced effects on palmitoleic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosapentaenoic acid and docosahekzaenoic acid belong to unsaturated fatty acid in both skin and muscle tissues.
Keywords: Onchorhynchus mykiss; fatty acid; cadmium chloride; muscle and skin tissues; enzymes